The Role of Business Dictionaries - Nimani, Valbone Zeqiraj (European Journal of Economics and Business Studies, 2016)
English language is an international language or one can freely say that it is an everyday language no matter which country you live in or which country you come from. We can say so, considering the fact that business has become one of the life neccesities and knowing that doing bussines means having to do with different people from all over the world, and the language used in every field is English. Nowadays no studies, no travelling, no business can be run without being able to speak English language. In response to these needs, this article is an attempt to provide a guided approach to ESP dictionaries design for business students at tertiary level.. When designing an English course, the primary issue is the analysis of learners’ specific needs and the appropriate literature that suits those needs. Learners want to learn EOP ( English for Occupational Purpose), EBE (English for Business and Economics), EAP (English for Academic Purposes) etc, all for instrumental reasons. Some learners are preparing for future jobs in which they will use English, whereas others want to learn it to improve their current job performance in dealing with particular partners or customers. All of these purposes can be achieved only by using the proper dictionary which will enable learners to learn their ESP in a faster and easier way. A bilingual dictionary is necessary due to the level of the students at the beginning. An english-english one is only used with advanced learners. It is absolutely necessary to use one, but very often teachers first have to teach learners how to take advantage of it and take time to work with examples on the different meanings depending on the context.
Keywords: EBE, entry, business, dictionary, translation, Anglicism, comparison, explanation etc